The International Criminal Court and United States opposition: a structural contradictions model - Rothe, Dawn (Crime, law and social change, 2006)
While the International Criminal Court (ICC) has been touted as the most fundamental development in international society to date, there has been relatively little criminological research examining the potential influence of the ICC. Additionally, criminologists have neglected the United States' responses to the ICC. Our purpose is to fill that gap by examining the United States' role in the development of, and subsequent reactions to, the ICC. Moreover, we draw upon Chambliss' Structural Contradictions Model to explicate processes within the development of International Law, thereby expanding its utility. We begin with a brief discussion of the most contentious elements of the ICC for the United States, sovereignty and jurisdiction, followed by a review of the theoretical model utilized in our analysis. We then discuss the role of the United States in the development of the ICC followed by the proceeding actions taken against the Court. We suggest how US withdrawal and legislative undermining of the ICC not only reflects the US ambiguous relationship with international law but also reveals some of the inherent limitations placed on the ICC as an international institution of formal social control. We conclude with a criminological analysis of the Court's potential based on the existing Rome Statute and the recent efforts of the U.S. to thwart its efficacy.